Rethinking Web-Based Writing Instruction Pedagogy: A Critical Literature Review - Amin Basir; Zakky Yavani (STIT Buntet Pesantren Cirebon, 2025)
This study aims to critically analyze the strategies, assessment practices, and challenges associated with web-based writing in EFL and ESL contexts, based on research published between 2015 and 2025. Using a Critical Literature Review (CLR) approach, the study systematically examined peer-reviewed journal articles, conference papers, and book chapters from reputable academic databases. The review identified key strategies that enhance learner engagement, such as collaborative writing tools, process-based approaches, and multimodal resources. Assessment practices have shifted toward formative, technology-enhanced methods, including peer feedback and digital portfolios, though issues related to validity and teacher readiness remain. Major challenges encountered include unequal access to digital tools, gaps in digital literacy, and academic integrity concerns. This review provides valuable insights for educators, learners, and researchers aiming to improve web-based writing instruction and assessment through informed, evidence-based practices.